Case report: Drug rash with eosinophilia and systemic symptoms syndrome in a patient with anti–interferon-γ autoantibody–associated immunodeficiency - Nie, Yuxue; Wang, Han; Dong, Xiying; Pan, Siqi; Zhang, Ting; Ran, Jun; Zhang, Ying; Fan, Junping; Zhang, Linqi; Wang, Jinglan (Frontiers in Immunology, 2022)
A 56-year-old Chinese woman with previous disseminated mycobacterium avium complex infection and recurrent cervical abscesses from Burkholderia cepacian visited our hospital. She was diagnosed with adult-onset immunodeficiency (AOID) and tested positive for interferon-γ-neutralizing autoantibody. Ceftazidime was administered as the initial antimicrobial treatment, which was later combined with sulfamethoxazole-trimethoprim (SMZ-TMP). She developed drug rash with eosinophilia and systemic symptoms (DRESS) syndrome after SMZ-TMP administration, and improved after withdrawal of the culprit antibiotic and systemic glucocorticoids treatment. Her cervical infection was eventually cured after combined therapy of long-term antibiotics and anti-IFN-γ autoantibodies (AIGA) titer-lowering treatments including glucocorticoids, rituximab and plasmapheresis. This is the first case of DRESS syndrome in the setting of AIGA-induced AOID and is worthy of notice.